2018
DOI: 10.1016/j.amjmed.2017.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Associates with Increased Right Ventricular Afterload and Remodeling in Pulmonary Arterial Hypertension

Abstract: Cumulatively, these data demonstrate that an increase in right ventricular afterload, beyond pulmonary vascular resistance alone, may influence right ventricular remodeling and provide a mechanistic link between the susceptibility to right ventricular dysfunction in patients with both diabetes mellitus and pulmonary arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
0
18
0
3
Order By: Relevance
“…Recently, we also reported that pulmonary arterial stiffness and elasticity are significantly higher in PH patients with DM than in PH patients without DM (Whitaker et al . ). These data suggest that there is a strong association between DM and the progression or severity of PH.…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 97%
“…Recently, we also reported that pulmonary arterial stiffness and elasticity are significantly higher in PH patients with DM than in PH patients without DM (Whitaker et al . ). These data suggest that there is a strong association between DM and the progression or severity of PH.…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 97%
“…fibrosis, oxidative stress, altered calcium homeostasis and substrate metabolism) [8][9][10]; through indirect effects via alterations in vascular function (e.g. arterial stiffening and microvascular dysfunction) [11]; and (or) through ventricular interdependence (i.e. structure, compliance, and function of the one ventricle, through direct mechanical interaction via septal wall and pericardium, may affect structure and function of the other ventricle) [3][4][5].…”
mentioning
confidence: 99%
“…Although fibrosis may be present in any organ of the body (Gilbert and Cooper, 1999;Patil et al, 2011), its involvement of the cardiovascular system is particularly prevalent in DM. While there may be more subtle processes involving the pulmonary arterial stiffness and cardiac right ventricle in association with pulmonary hypertension (PH) in DM (Grinnan et al, 2016;Whitaker et al, 2018), metabolic dysfunction has been identified in particular (Irwin et al, 2014;Lai et al, 2019). Up to 30% of patients with HFpEF have DM (Piccini et al, 2004).…”
Section: Tg2 In Hyperglycemia Mediated Cardiopulmonary Remodelingmentioning
confidence: 99%